Pengaruh Pelatihan Dan Pengawasan Terhadap Kinerja Pegawai Pada Lembaga Penyiaran Publik TVRI Sumatera Utara - Azli Tri Wardana; Rini Astuti; Sri Murniyanti (CERED Indonesia Institute, 2020)
The purpose of this study was to determine and analyze the effect of training on employee performance, to know and analyze supervision on employee performance and to know and analyze the effect of training and supervision on employee performance at the public broadcaster TVRI North Sumatra. The approach used in this research is an associative approach. The population in this study were employees of the North Sumatra TVRI Public Broadcasting Institution in the field of Business Development & Programs and Engineering, totaling 98 respondents. Data collection techniques in this study used interview and questionnaire techniques. Data analysis techniques in this study used the Classic Assumption Test, Multiple Regression, Hypothesis Test (t test and f test), and the Coefficient of Determination. Data processing in this study uses the SPSS (Statistic Package for the Social Sciens) software program. Partially, it is known that the training has a positive and significant influence on the performance of employees at the public broadcaster TVRI North Sumatra Utara. Partially, it is known that supervision has a positive and significant influence on the performance of employees at the public broadcaster TVRI North Sumatra. Simultaneously it is known that training and supervision have a positive and significant effect on employee performance at the TVRI Public Broadcasting Agency North Sumatra